Examining the relationship between multidimensional parenting styles and digital parenting awareness levels of parents - Sumeyra, Akkaya; Burcu, Gezer Sen; Metin, Kapıdere (Birlesik Dunya Yenilik Arastirma ve Yayıncilik Merkezi, 2021)
This article provides an overview of the relationship between parents' multidimensional parenting styles and digital parenting awareness levels. The article summarizes the structure of parenting styles that exist with the social changes in the 21st century and the research findings on parents' awareness levels. In the study, the relational screening model was used to examine the relationship between parents' multidimensional parenting styles and their digital parenting awareness levels. As a result of examining the multidimensional parenting styles of the participants in the study, it was determined that the proactive average had the highest value. A positive correlation was found between total digital parenting awareness and proactive, positive reinforcement, supportive approach, and cordial relationship. In addition, it was determined that hostility and low control decreased the total level of digital parenting awareness, while positive reinforcement increased the total level of digital parenting awareness. Another result of the research is that hostility reduces the level of protection from risks, while positive reinforcement increases the level of protection from risks. © 2021 Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi. All rights reserved.
Keywords: Digital parenting; Multidimensional parenting styles; Primary education